Perancangan User Experience Aplikasi Pelayanan Pelanggan menggunakan Metode Human Centered Design Studi Kasus : Bengkel Victoria Motor - Dozi Imam Nursyahbani; Agi Putra Kharisma; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Victoria Motor Workshop is one of the workshops located in Malang City. This workshop, which has been established for dozens of years, already has good trust from customers. However, some customers of the Victoria Motor workshop have problems when they want to service motorbikes during working hours such as, when servicing a motorbike takes a long time, there is no shuttle service for motorbike servicing, then there is no quick notification when the motorbike service has been completed. This study aims to design a User Experience Application for customer service as a solution that has good usability and user experience values. The Human Centered Design approach is used by paying attention to the User Experience elements. Starting from analyzing the user context, analyzing user needs, and creating solution designs. Evaluation of the design using Usability Testing resulted in an effectiveness value of the success rate for the customer version of 97.915%, for the technician version of 93.75%, and for the admin version of 91.65%. The average task Completion Rate is 94.43%. the efficiency of the Victoria Motor customer service application was 93.45% for the customer version, 63.95% for the technician version, and 61.1% for the admin version. And from the error aspect, it is known that the error rate for the Victoria Motor customer service application is 0% for the customer version, 0% for the technician version, and 0% for the admin version. Customer satisfaction gets a score of 89.2% from the system usability scale test, which means that the acceptability range gets an acceptable score, then the grade scale gets grade B, and the adjective rating gets excellent. Thus, the design solution has a positive value in terms of User Experience and Usability.